Rosalie Gascoigne : a catalogue raisonné - Gascoigne, Martin (ANU Press, The Australian National University, 2019)
Rosalie Gascoigne (1917-1999) was a highly regarded Australian artist whose assemblages of found materials embraced landscape, still life, minimalism, arte povera and installations. She was 57 when she had her first exhibition. Behind this late coming-out lay a long and unusual preparation in looking at nature for its aesthetic qualities, collecting found objects, making flower arrangements and practising ikebana. Her art found an appreciative audience from the start. She was a people person, and it pleased her that through her exhibiting career of 25 years, her works were acquired by people of all ages, interests and backgrounds, as well as by the major public institutions on both sides of the Tasman Sea.